Panic Buying and Hoarding of Medicine During the Covid-19 Pandemic in the Perspective of Islamic Ethics - Muhammad Nurul Alim; Ruslan Husein Marasabessy (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2023)
This study aims to analyze Islamic ethics towards panic buying and hoarding of medicines during the Covid-19 pandemic. Queues at pharmacies were seen in June-July 2021 as a phenomenon of public panic against Covid-19. This study uses an interpretive descriptive qualitative approach. Research data were collected through literature study. The results show that there are Islamic ethics for sellers and buyers so as not to harm the community. Islamic ethics for sellers are (1) Fear of Allah so as not to be punished sinful; (2) Not taking advantage of the community's distress during the Pandemic; (3) Be qanaah by not refusing a small profit. Islamic ethics for buyers are : (1) Fear of Allah in order to accept disaster as Allah's will; (2) The rationality of consumption of Muslim families during the pandemic; (3) Prioritizing at-ta'awun or helping each other in emergency situations; (4) Be satified so that someone doesn't buy more than his need. This research is expected to be useful for sellers and consumers to behave Islamic ethics in responding to panic buying and ihtikar.